Percepção de agentes do mercado de capitais sobre os fatores que influenciam o investimento em Brazilian Depositary Receipt (BDR) - Lima Filho, Adelmo Ferreira de (2018)
This work is a mixed study aimed at capturing the perception of a selected group of capital market agents about the factors that influence the Brazilian Depositary Receipt (BDRs) investment in the Brazilian market. This issue is relevant because, since its implementation, the BDR has been presented to the market as a possibility to elaborate new strategies for investment diversification, arbitrage, fundraising, among other reasons. Thus, the objective of this study is to present a view of the BDR in the Brazilian market and to answer the research question of which factors influence the investment in BDRs in the Brazilian capital market. To achieve this objective, a survey was carried out using the mixed method, combining data collected through a pre-defined questionnaire and qualitative data through interviews with a selected group of capital market agents being brokerage firms, assets, professional investors, investment banks, depository institutions and law firms specializing in capital markets in Brazil. The results bring: first, a historical view of the BDRs in Brazil; second, present an analysis on the factors that influence the use of the BDRs in the capital market in Brazil; Third, it contributes to market practice, revealing aspects of BDRs; fourth, presents to which market and target public this asset is currently directed based on a vision of the advantages and disadvantages of investing in BDRs.